STRATEGI RUMAH BATIK ANDALAN DALAM MELAKUKAN EKSPOR BATIK BONO KE TIONGKOK TAHUN 2016-2019 - Delin Belani Ginting; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study discusses how Rumah Batik Andalan is doing to promote and export Batik Bono to China. One area that already owns and produces its own batik is Pelalawan Regency in Riau province. Bono batik describes the bono wave in Pelalawan district. This research uses liberalism perspective and group level analysis, International Trade theory. The researcher uses a literature study research method by collecting data from books, academic journals, official documents, laws, sources from the internet related to research on the Mainstay Batik House Strategy in Exporting Bono Batik to China in 2016 – 2019 and researchers also use primary data namely by direct interviews with the head of Rumah Batik Andalan and field surveys. The results of this study indicate the Strategy of Rumah Batik Andalan in Exporting Batik Bono to China in 2016 – 2019, namely by providing support from the Pelalawan district government for the existence of the mainstay batik house export, and Rumah Batik Andalan being a foster partner of the Riau Andalan Pupl and Paper Company or APRIL, and also do promotions through social media such as Instagram and Facebook. Direct sales and have oulets at Sultan Syarif kasim II. Keywords : Export, Mainstay Batik House, Foster Partners, Batik Bono, Social Media, International Trade.